Full-optical photoacoustic imaging using speckle analysis and resolution enhancement by orthogonal pump patterns projection - Vorobev, Viktor; Weidmann, David; Agdarov, Sergey; Beiderman, Yafim; Shabairou, Nadav; Benyamin, Matan; Klämpfl, Florian; Schmidt, Michael; Gorin, Dmitry; Zalevsky, Zeev (Scientific Reports, 2023)
This paper presents an approach for achieving full optical photoacoustic imaging with enhanced resolution utilizing speckle pattern analysis. The proposed technique involves projecting patterns derived from binary masks corresponding to orthogonal functions onto the target to elicit a photoacoustic signal. The resulting signal is then recorded using a high-speed camera and analyzed using correlation analysis of the speckle motion. Our results demonstrate the feasibility of this optical approach to achieve imaging with enhanced resolution without the need for physical contact with the target, opening up new possibilities for non-invasive medical imaging and other applications.
CRIS-Team Scopus Importer:2023-11-10